(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
Jewellery has been used over the ages to adorn belts, serving a variety of functions as well as bearing numerous symbolic meanings. In addition to their functional uses in fastening clothes, belts in the Middle Ages also declared a person s professional status or military rank and the jewellery on medieval belts often incorporated insignias of nobility. These roles of belts in the Middle Ages are attested to by archaeological finds Fig. 1-4 by portraits in medieval frescoes, particularly those from the 14th and 15th century, Fig. 5, 6, as well as by various written sources. A specific metal addition is found on belts discovered among archaeological materials from Macedonia in the 16th century onwards—the metal belt-buckle. Fig. 7 The presence of belt buckles is even more noticeable in findings from the 17th and 18th centuries in the ruins of settlements, in graves and—more rarely—as burial offerings Fig. 8-10 Macedonian metal buckles from the 18th to the 20th century form an important part of ethnological collections and were among the most remarkable, precious and luxuriantly crafted jewellery additions of that time. Buckles were worn both by women as a decoration to their clothing, particularly in bridal wear, and by men as an addition to everyday secular or ceremonial and priestly vestments Fig. 11-15,17ab, 18 Metal buckles were used both by Christians and Moslems. The most appropriate approach to the scientific interpretation of the various metal decorations on belts from the Middle Ages to the period of the revival in Macedonia is an interdisciplinary approach that makes use of methods from the fields of archaeology, history, art history, and—of course—ethnology.